Attack ! : Kunst und Krieg in den Zeiten der Medien. - Mackert, Gabriele; Matt, Gerald; Mattl, Siegfried; Miessgang, Thomas; Robnik, Drehli (Wien : Kunsthalle, 2003)
A-1 53167 ; Andjelkovic, Dejan ; association APSOLUTNO ; Banner, Fiona ; Bernstrup, Tobias ; Brudermann, Nin ; Bugaev Afrika, Segei ; Claerbout, David ; Debord, Guy ; Djuric, Uros ; Fahlström, Öyvind ; Fend, Peter ; Fodor ; Green, Renée ; Hamilton, Richard ; Zhuang Hui ; Korpys, Andree ; kuda.org ; Landau, Sigalit ; Löffler, Markus ; Marker, Chris ; Mayer, Hans-Jörg ; Motti, Gianni ; Nes, Adi ; Novotny, Franz ; Pobitzer, Klaus ; Radovanovic, Jelica ; Ressler, Oliver ; Riello, Antonio ; Rosler, Martha ; Schorr, Collier ; Schröter, Erasmus ; Solakov, Nedko ; Spero, Nancy ; Steiner, Herwig ; Tillmans, Wolfgang ; Torsson, Palle ; Virilio, Paul ; Wang Du
Attack ! : Kunst und Krieg in den Zeiten der Medien, Kunsthalle Wien, Wien, 2003-05-23. 2003-09-21
boek